An unusual presentation of intestinal duplication mimicking torsion of Meckel’s diverticulum: a rare report of a pediatric case - Makoto Matsukubo; Mitsuru Muto; Chihiro Kedoin; Mayu Matsui; Masakazu Murakami; Koshiro Sugita; Keisuke Yano; Shun Onishi; Toshio Harumatsu; Koji Yamada; Waka Yamada; Tatsuru Kaji; et al. (Surgical Case Reports, 2022)
Abstract Background Enteric duplication is a congenital disease that occurs throughout the entire gastrointestinal tract. Although it may sometimes cause intestinal volvulus, a few reports have described cases of enteric duplication twisted on itself. We experienced a rare pediatric case of long-segment tubular ileal duplication showing torsion. Torsion of enteric duplication is extremely rare. We herein report a pediatric case showing unusual torsion of ileal duplication requiring emergency surgery. Case presentation A 3-year-old boy presented with abdominal pain and vomiting. Contrast-enhanced computed tomography (CT) revealed a cystic luminal structure with a blind end and fluid collection in the pelvic cavity. CT also showed no findings of ileus or intestinal dilatation except for a cystic luminal structure. The preoperative diagnosis was torsion of Meckel’s diverticulum. The patient underwent emergent explorative diagnostic laparoscopy. As a result, a necrotic luminal structure and bloody ascites were recognized, and small-scale laparotomy was performed. Long-segment ileal duplication was recognized. The long-segment tubular ileal duplication shared the anti-mesenteric side of the intestinal wall along one-third of its length. The residual two-thirds of its length was free from the ileum and its blind end was twisted in a manner that looked similar to Meckel’s diverticulum. Normal ileum and the duplication, including the twisted necrotic portion, were resected, and ileal anastomosis was performed. The postoperative course was uneventful. A pathological examination confirmed the definitive diagnosis of enteric duplication. Conclusions We reported the unusual presentation of intestinal duplication mimicking torsion of Meckel’s diverticulum. Enteric duplication shows various clinical symptoms and presentations. We must understand that the classification of digestive enteric duplication is diverse with a variety of associated clinical symptoms.